2003
DOI: 10.1074/jbc.m209279200
|View full text |Cite
|
Sign up to set email alerts
|

Sensitizing Anthrax Lethal Toxin-resistant Macrophages to Lethal Toxin-induced Killing by Tumor Necrosis Factor-α

Abstract: Macrophages from different inbred mouse strains exhibit striking differences in their sensitivity to anthrax lethal toxin (LeTx)-induced cytolysis. Although LeTxinduced cytolysis of macrophages plays an important role in the outcome of anthrax infection, the sensitivity of macrophages in vitro does not correlate with in vivo susceptibility to infection of Bacillus anthracis. This divergence suggests that additional factors other than LeTx are involved in the cytolysis of LeTx-resistant macrophages in vivo. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
87
3

Year Published

2004
2004
2010
2010

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(100 citation statements)
references
References 44 publications
10
87
3
Order By: Relevance
“…Macrophage susceptibility to LT killing appears to be dependent upon maturation state, and certain external stimuli, like lipopolysaccharide (LPS), can confer susceptibility to C57BL/6 macrophages. 24,42,43 Moreover, we recently showed significant LT killing of another myeloid lineage cell type, dendritic cells (DCs), derived from BALB/c and C57BL/6 mice, as well as human PBMCs. 18 Due to the similar responses of macrophages and DCs from BALB/ c mice to LT treatment, we hypothesized that, like C57BL/6 DCs, C57BL/6-derived macrophages may be susceptible to LT-mediated cell killing.…”
Section: Susceptibility Of Murine Macrophages To Lt Killingmentioning
confidence: 99%
See 4 more Smart Citations
“…Macrophage susceptibility to LT killing appears to be dependent upon maturation state, and certain external stimuli, like lipopolysaccharide (LPS), can confer susceptibility to C57BL/6 macrophages. 24,42,43 Moreover, we recently showed significant LT killing of another myeloid lineage cell type, dendritic cells (DCs), derived from BALB/c and C57BL/6 mice, as well as human PBMCs. 18 Due to the similar responses of macrophages and DCs from BALB/ c mice to LT treatment, we hypothesized that, like C57BL/6 DCs, C57BL/6-derived macrophages may be susceptible to LT-mediated cell killing.…”
Section: Susceptibility Of Murine Macrophages To Lt Killingmentioning
confidence: 99%
“…24 In contrast, macrophages from C57BL/6 mice have largely served as the prototype for LT-resistant macrophages. 24,[32][33][34] A recent report suggested that a highly polymorphic gene, Nalp1b, controls LT susceptibility in murine macrophages. 32 Nalp1b is a critical immune protein that functions in assembling the inflammasome, a multimeric complex, which contains and activates caspase-1.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations